2006
DOI: 10.1111/j.1083-6101.2004.tb00286.x
|View full text |Cite
|
Sign up to set email alerts
|

Information Exchange in Virtual Communities: A Comparative Study

Abstract: Burnett's (2000) typology of information exchange in virtual communities attempts to provide a framework for examining the range of activities undertaken by participants in such communities. This study is the first in a series to apply the typology to specific virtual communities, in an effort to assess its accuracy against the day‐to‐day interactions to be found in two online communities. Through a comparison of these two communities using the typology, revisions to the typology are proposed which will allow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
197
0
19

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(221 citation statements)
references
References 13 publications
5
197
0
19
Order By: Relevance
“…For instance, Burnett and Buerkle (2004) distinguished between informational and noninformational collaborative behavior and reported that a high percentage of the posts involved queries and answers. This type of information sharing in virtual communities was evident as early as 1985, with the Experts on Well (an early online community), which was described by Rheingold (2000, p.50): "If you have a problem or a question… you pose it.…”
Section: Qanda Sites As Virtual Communitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Burnett and Buerkle (2004) distinguished between informational and noninformational collaborative behavior and reported that a high percentage of the posts involved queries and answers. This type of information sharing in virtual communities was evident as early as 1985, with the Experts on Well (an early online community), which was described by Rheingold (2000, p.50): "If you have a problem or a question… you pose it.…”
Section: Qanda Sites As Virtual Communitiesmentioning
confidence: 99%
“…Both explicit norms (which are codified) and implicit norms (that emerge through the day-to-day interactions) define the acceptable social behaviors in a specific virtual community (Burnett & Bonnici, 2003). These norms help socialize "newbies" into the community and help the community handle deviant behaviors (Burnett & Bonnici, 2003;Burnett & Buerkle, 2004). "Participants [in Answerbag] translate their knowledge, experience and opinions into content that both adheres to and continuously redefines the standards of the community."…”
Section: Qanda Sites As Virtual Communitiesmentioning
confidence: 99%
“…This result strongly recommends that culture awareness is necessary to improve management of cross-cultural online communication (Burgmann, Kitchen & Williams, 2006). Several studies analyze content of websites according to a cross-cultural perspective (Burnett & Buerkle, 2004), cultural adaptation of websites improving effectiveness of companies' internationalization strategies. Recent studies stress that, in globalized markets, the ability to manage cultural diversity is a strategic competence that companies have to employ for designing their websites.…”
Section: A Hofstede's Cultural Dimensions Theorymentioning
confidence: 99%
“…Burnett (2000) divide o comportamento dos membros em não interativos -aqueles que apenas leem, não deixando mensagens, caracterizando um comportamento de busca de informações -e interativos -aqueles que geram conteúdo. Essa classificação é similar a de Algesheimer e Dholakia (2006) em "entusiastas" ou "indivíduos que obtêm benefícios da interação social sem contribuir".…”
Section: Constructos De Interesse E Hipóteses De Pesquisaunclassified